Chicano! : the history of the Mexican American civil rights movement - Rosales, Francisco A. (Francisco Arturo) (Hispanic civil rights series., 1997)
Studies four major episodes in the history of the Mexican-American civil rights movement looking at efforts to enforce the Treaty of Guadalupe Hidalgo; immigrant experiences with discrimination; the strides made by children of immigrants with no ties to Mexico; and the evolution of the Chicano Movement and its legacy.